Somatotipo e composição corporal de árbitros de futebol do nordeste e sul do Brasil - Vieira, Caio Max Augusto; Costa, Eduardo Caldas; Da Silva, Alberto Inácio; Sedorko, Clóvis Marcelo (HU Revista, 2016)